A Novel Control Strategy of Indirect Matrix Converter Using Space Vector Modulation - Kuldeep Behera; Subrat Behera (Institute of Advanced Engineering and Science, 2016)
This paper introduces a control scheme of Indirect Matrix Converter which includes space vector modulation to stabilize the frequency variations. The terminal voltage and frequency of any synchronous machine can be controlled easily with this scheme. Further the control strategy is proposed and implemented in Matlab/Simulink Embedded system which gives significant better performance compared to conventional control technique like better Total Harmonic Distortion (THD), more output voltage with same Modulation Index, less switching stress and less switching loss. This method might prove effective for wind energy conversion system using DFIG as the DFIG speed is close to synchronous speed. The complete control strategy is verified using MATLAB/Simulink.